"Insects as an Indicator for Environmental Pollution". Issue 2 (30th March 2021) - Parikh, Garvita; Rawtani, Deepak; Khatri, Nitasha
Abstract: Bioindicators have been generating great interest in environmental pollution research. The main goal of research on bioindicators is to identify species that would reliably indicate disturbances in the environment as well as show the effects of those disturbances on other species or the overall biodiversity. Insects are especially useful to assess the effects of anthropogenic activities on the terrestrial ecosystem as well as aquatic system and atmosphere, because they are in close contact with toxic elements present in soil, water and air. In this article we have highlighted the importance of the insects as a beneficiary in monitoring of environmental pollution and assessment of pollutants. We have mainly focused on insects as important indicators of change in air, water and soil quality. Most insects like beetles, ants, honeybees, and butterflies are used as biological indicators in this study because they are sensitive to even a slight change in the environment and also used in monitoring of various pollutants in environment.